PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN BIAYA PADA PT. GARUDA INDONESIA CABANG MAKASSAR - Nur Aisyah (AkMen JURNAL ILMIAH, 2016)
The aim of the study was to know the application of cost accounting at PT. Garuda Indonesia Branch Makassar. The data used is the qualitative and quantitative data. Source data used are primary data obtained by collecting data from companies, the data for which annual financial statements consisting of three divisions, namely the Finance Division, Marketing Division, and the Division of stations as well as secondary data obtained by direct observation to the field, study the good library of books, as well as from internet sites that are relevant to the subject of research, and conduct interviews with the parties associated with the research. The analytical method used is comparative descriptive that describes and compares the application of cost accounting done at PT. Garuda Indonesia Makassar branch with accounting liability costs by Mulyadi. The results showed that the application of cost accounting done at PT. Garuda Indonesia Makassar branch in accordance with the application of accounting costs by Mulyadi.